3D surface crack characterization by eddy current array image and a fast algorithm search - Abdou, Abdelhak; Bouchala, Tarik; Abdelhadi, Bachir; Guettafi, Amor (Journal of Electrical Engineering, 2023)
Nowadays, 3D eddy current nondestructive characterization of crack and corrosion defects while using ECA remains an industrial challenge because the obtained image permits to determine only the 2D defect shape. Consequently, this article is devoted to determine directly the crack length and width by eddy current images through sensor array. Afterwards, we extract the maximal impedance amplitude to estimate the crack depth while using the deterministic algorithm that we have recently developed. In fact, the obtained results have demonstrated the effectiveness and the reliability of the proposed method.